Prevalence of Overweight and Obesity among the School-Going Children (6-12 Years) of Urban and Rural Areas in Bangladesh (The Journal of Ad-din Women's Medical College, 2024)
Introduction: Childhood obesity becomes an epidemic worldwide which is escalating as a major health burden in developed as well as in developing countries. The obesity in childhood appears to be an increased risk of subsequent metabolic, systemic and psycho-social morbidities. The transitions in the dietary habit and sedentary lifestyle are the major risk factors along with some genetic involvement. Prevalence survey is necessary to know about the present incidence and the trend to combat childhood overweight and obesity. Objectives: Aim of this study is to assess overweight and obesity among urban and rural school-going children of 6-12 years old. Materials & Methods: A prospective observational study was carried out from March 2013 to May 2014 by the Department of Pediatrics, Bangabandhu Sheikh Mujib Medical University, Dhaka and subjects were from two schools of rural and urban areas of Bangladesh. Total 365 children aged between 6-12 years were included. Weight and height of all available students were measured, BMI was calculated and nutritional status was measured by using CDC growth chart. Results: Proportion of overweight and obesity among all selected students were 35 (9.6%) and 40 (11%) respectively. In Rural area 5 (2.6%) and 3 (1.5%) children were overweight and obese respectively whereas in Urban area, 30 (17.6%) and 37 (21.8%) children were overweight and obese respectively. The proportions were significantly higher than in rural area. Conclusion: Overweight and obesity are in high proportion among urban school going children.The Journal of Ad-din Women's Medical College; Vol. 12 (1), Jan 2024; p 9-14